A Modem Introduction to Indian Logic - V K Bharadwaja (Journal of Dharma, 1976)
This absorbingly interesting book comprises eleven chapters in- cluding the one numbered V-A. There is an historical introduction pp. 1-13) followed by a discussion on the notion of pramana (pp. 14-22) and on knowledge and language (pp. 23-42). The third and the forth chapters analyse judgements, propositions and functions (pp 43-62) and identify Indian counterparts of several truth-functional operators in Indian Logic. The theory of definition and the concept of upddbi also are discussed here (pp. 63-71). The next three chapters are devoted to a detailed discussion on negation (pp. 72-86), samanya (pp. 87-95) and the logic of relations (pp. 96-110). The two chapters that follow are excellent essays on the theory of in- ference (pp. 111-161), and the inductive elements in Indian Logic (pp. 162-183).